Case Report: A Novel Heterozygous Mutation of CD2AP in a Chinese Family With Proteinuria Leads to Focal Segmental Glomerulosclerosis - Yu-Xing Liu; Yu-Xing Liu; Yu-Xing Liu; Yu-Xing Liu; Ai-Qian Zhang; Fang-Mei Luo; Fang-Mei Luo; Yue Sheng; Yue Sheng; Chen-Yu Wang; Chen-Yu Wang; Yi Dong; et al. (Frontiers Media S.A., 2021)
Idiopathic focal segmental glomerulosclerosis (FSGS) is a relatively frequent kidney disorder that manifest clinically as proteinuria and progressive loss of renal function. Genetic factors play a dominant role in the occurrence of FSGS. CD2-associated protein (CD2AP) is an adapter molecule and is essential for the slit-diaphragm assembly and function. Mutations in the CD2AP gene can contribute to FSGS development. Here, we describe a Chinese family of four generations with unexplained proteinuria. The proband, a 12-year-old boy, was diagnosed as FSGS. Whole-exome sequencing (WES) revealed an unknown frameshift insertion mutation (p.K579Efs*7) of CD2AP gene that leads to a truncation of CD2AP protein. Bioinformatics strategies predicted that the novel mutation was pathogenic. The mutation was absent in either healthy family members or our 200 healthy controls. In summary, we used WES to explore the genetic lesion of FSGS patients and identified a novel mutation in CD2AP gene. This work broadens the mutation spectrum of CD2AP gene and provides data for genetic counseling to additional FSGS patients.